Festival Anak Sholeh Sebagai Sarana Penanaman Nilai Religius Di Dusun Kunden, Sendangsari, Pajangan, Bantul - Markhamatun Ni'mah; Lia Hikmatul Maula; Fakhri Azhar; Ayu Anggraeni Kusuma Jati; Devita Andriana; Rosita Murti Pratiwi; Muh Abdul Hasan; Salwah Salwah; Irma Novitasari; Jihan Rahmahwati; Pingky Veronica; Zuhro Aida al Ayubi; An-Nisa Apriani (Universitas Alma Ata, 2023)
The Saleh Children's Festival is one of the collaborative programs organized by the Alma Ata University Community Service Program students in the hamlet of Kunden. The purpose of holding this pious children's festival program is 1. to increase enthusiasm in learning Islam, 2. to develop interests and talents in the field of religion, 3. to increase the self-confidence of the children of the Kunden village. In the implementation of the pious children's festival program, there are 4 categories of competitions, namely: Adhan competition, short letter memorization competition, daily prayer memorization and calligraphy coloring. the method of implementing the activity is by analyzing the needs of children of primary school age, planning, implementing, and evaluating as well as following up on the activities that have been taught. The results of this pious children's festival program are so that the children of Dusun Kunden are more enthusiastic in teaching Islam, then the children of Dusun Kunden are also bolder to show their talents and increase their self-confidence after participating in the pious children's festival program. Keywords: Sholeh Children Festival, Keywords: Festival Anak Sholeh, Race, Method